Le monde Gothique de Le Fanu : cryptonymes et mots étrangers - Christine Berthin (Cahiers Victoriens et Edouardiens)
This article examines the gothic uses of foreign words and foreign names in the fiction of Le Fanu. The revenant, the villains in Uncle Silas, or the vampire in Carmilla are systematically associated with foreign words and idioms. In Uncle Silas, French is used in connection with the return of an ill-buried and ill-repressed personal and collective past. In Carmilla, German cryptonyms point to secret alternative messages that remain partly untranslatable and need to be read against the grain of the narrative. More than a genre, the Gothic is a poetic subversion of the Symbolic. Foreign words and foreign names are an essential part of this poetic: their function is not denotative, and they do not contribute to surface meaning. On the contrary, they arrest and question meaning and open up the possibility of other voices in the text.